DOMESTIC INSTITUTIONAL OWNERSHIP DAN FOREIGN INSTITUTIONAL OWNERSHIP TERHADAP LIKUIDITAS SAHAM (Studi pada Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Hamdani Hamdani; Maulizar Maulizar; Yetty Tri Putri; Halimatus Sa’diyah (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This research was conducted to deterime the influence of ownership structure, domestic institutional ownership and foreign institutional ownership from stock market liquidity. Control variable in this research is size measure by market capitalization. This research use a quantitative approach using statistical tools in the form of multiple linear regression. This study use secondary data from manufacture firm wich fulfill the requirement and listing in Indonesia Stock Exchange from 2009-2010. The result of this study conclude that domestic institutional ownership has a significant negative influence on stock market liquidity wich measured by depth but domestic institutional ownership wich measured by relative spread hasn’t significant influence on stock market liquidity. The second result of this study is foreign institutional ownership has a significant negative influence on stock market liquidity wich measured by depth and also has a significant positive influence on market likuidity wich measured by relative spread. Control variable has varied influence on stock market liquidity. Keywords :       Domestic institutional ownership, foreign institutional ownership, size, market capitalization, stock market liquidity,  depth,  relative spread.